Particulate Contamination in Single-Dose Parenteral Antibiotics in Iran: Parenteral antibiotics particulate contamination - Cheraghali, Majid; Jamei, Forough; Khairollahi, Koulsoum; Cheraghali, A. Majid (Iranian Journal of Pharmaceutical Sciences, 2005)
In order to ensure the safety of parenterals, international pharmacopoeias and national standards have set up stringent guidelines and standards. Particulate contamination is a potential health risk caused by intravenous injection of particles large enough to potentially clog the small arteries. Particles could be produced through manufacturing and packaging or even dispensing of the pharmaceuticals. The nature of the particles are varied and could be of drug itself, packaging debris, rubber, plastic, cotton, fiber and glass particles, which might be produced during the breakage of an ampoule. In this study, some of the small volume parenterals available in Iranian drug market have been investigated for the presence of particles. Although, most of the tested samples passed national standard tests for particulate contamination of small volume parenterals, 40% of the samples were rejected using the same protocols. Therefore, it appears that particulate contamination of parenterals creates an additional source of risk for patients who receive these medications, intravenously.